The Effect of Learning Cycle 5E on Critical Thinking Skills for Junior High School Students - Erlis Miarti; Neni Hasnunidah; Abdurrahman Abdurrahman (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2021)
This study aimed to find out the influence of the 5E Learning Cycle on the critical thinking skills of SMPN 1 Talangpadang VII graders. This study also aimed to determine the significance level of the two methods in improving critical thinking skills. One of the efforts is implementing the 5E learning cycle (Engagement, Exploration, Explanation, Elaboration, Evaluation). This study used a quasi-experimental with the matching-only pretest-posttest control group design. The population was all VII graders, while the samples were VII3 and VII4 students, where VII3 was the experimental class, and VII4 was the control class. The instrument used in this study was an essay test on critical thinking skills. The data underwent normality test using Kolmogorov Smirnov and homogeneity test using homogeneity of variances. Based on the t-test using the Independent Sample Test with SPSS statistics 21.0, the significance was 0.00 or less than 0.05, showing the influence of the 5E Learning Cycle on students' critical thinking skills.